Compliance of Statin Therapy in HyperEpidemic Patients - liver Noreen Irum, Bharat Lai, Habibuilah Shaikh, Masood Ahmed , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2017)
Objective: To determine the compliance of statin therapy in hyperlipidemic patients. Methods: This cross-sectional study was conducted in Pharmacology and Therapeutics Department, Peoples University of Medical and Health Sciences for Women Nawabshah from January to June 2015, in collaboration with Department of Cardiology & Medicine PMC Hospital Nawabshah. Total 100 Hyperlipidemic patients on Statin Therapy were enrolled in the study by convenience sampling. Morisky Scale was used for measurement of compliance. Results: Out of 100 patients enrolled the mean age of the patients was 49.45± 9.72 years. The age range most commonly affected is 51-70 years i-e; 56% and 31-50 years 44%. The mean cholesterol level were 231,83±15.9 mgldl. The statin therapy compliance was compared with age range, gender, and socioeconomic status. Statin therapy compliance was achieved in age groups, gender and socio,- economic status which revealed >80% PDC (proportion of days covered) response however results were not statistically significant p value-0.725, 0.726 and 0.056 respectively. Conclusion: Factors affecting compliance showed good adherence among both genders, and in high risk population particularly above age of 50 years. The compliance of statin Therapy was observed more in middle and higher class but slightly less compliance seen in the lower class probably due to non-affordability.